Altered expression of NCAM in hippocampus and cortex may underlie memory and learning deficits in rats with streptozotocin-induced diabetes mellitus - Baydas, G; Nedzvetskii, VS; Nerush, PA; Kirichenko, SV; Yoldas, T (Pergamon-Elsevier Science Ltd, 2003)
Neurological and structural changes are paralleled by cognitive deficits in diabetes mellitus. The present study was designed to evaluate the expression of neural cell adhesion molecules (NCAM) in the hippocampus, cortex and cerebellum and to examine cognitive functions in diabetic rats. Diabetes was induced in male albino rats via intraperitoneal streptozotocin injection. Learning and memory behaviors were investigated using a passive avoidance test and a spatial version of the Morris water maze test. NCAM expression was detected in the hippocampus, cortex and cerebellum by an immunoblotting method. The diabetic rats developed significant impairment in learning and memory behaviours, as indicated by deficits in passive avoidance and water maze tests as compared to control rats. Expression of NCAM 180 and 120 kDa were found to be higher in hippocampus and cortex of diabetic rat brains compared to those of control, whereas expression of NCAM 140 kDa decreased in these brain regions. Our findings suggest that streptozotocin-induced diabetes impairs cognitive functions and causes an imbalance in expression of NCAM in those brain regions involved in learning and memory. Altered expression of NCAM in hippocampus may be an important cause of learning and memory deficits that occur in diabetes mellitus. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: diabetes; STZ; learning; memory; NCAM; hippocampus; cortex